2015
DOI: 10.1007/s00394-015-1027-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes of serum adipocytokines and body weight following Zingiber officinale supplementation in obese women: a RCT

Abstract: In conclusion, our findings demonstrate a minor beneficial effect of 2 g ginger powder supplementation for 12 weeks on weight loss and some metabolic features of obesity. However, given the lack of data in this area, ongoing clinical trials are needed to further explore ginger's effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
3
38
0
2
Order By: Relevance
“…Furthermore, this is also in line with a recent study by Lopez et al [24] who demonstrated that a supplement containing caffeine and capsaicin for 8 weeks accentuated body weight and fat loss during a weight loss program. A significant decrease in BMI was also seen following the supplementation with 2 g/day of ginger powder among obese women for 12 weeks [10]. Green tea, capsaicin and ginger appear to complement each other by acting on the various pathways of the sympathetic nervous system at the cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this is also in line with a recent study by Lopez et al [24] who demonstrated that a supplement containing caffeine and capsaicin for 8 weeks accentuated body weight and fat loss during a weight loss program. A significant decrease in BMI was also seen following the supplementation with 2 g/day of ginger powder among obese women for 12 weeks [10]. Green tea, capsaicin and ginger appear to complement each other by acting on the various pathways of the sympathetic nervous system at the cellular and molecular levels.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the consumption of a dietary supplement containing epigallocatechin gallate (EGCG), capsaicins, piperine and L-carnitine for 8 weeks among overweight subjects decreased insulin resistance and LDL-cholesterol levels [9]. A significant decrease in body mass index (BMI), serum insulin, insulin resistance and a significant increase in insulin sensitivity were also seen following the administration of 2 g/day of ginger powder among obese women for 12 weeks [10]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, an early study showed that dietary intake of ginger could enhance thermogenesis and reduce feelings of hunger . Moreover, ginger supplementation showed a beneficial effect on weight loss and some obesity‐associated parameters in overweight and obese adults …”
Section: Preventive Effects Of Ginger On Metabolic Diseasesmentioning
confidence: 99%
“…For instance, digestive disorder, hypertension, inflammation, and cold are common diseases where ginger can be used [11]. The marker compounds contained in ginger, particularly gingerol and shogaol, have been reported exhibit important antioxidant properties with remarkable anticancer, and antimutagenic effect [12], analgesic [13], inhibit melanoma [11], inhibit platelet aggregation [14], antihyperlipidemia [15], antidiabetes [16], ameliorate renal and pancreas damage [17], and so on. Certain compounds contained in (Z. officinale) demonstrate synergistic effect as auxiliary chemical agent against on C. albicans, Enterococcus faecalis, Escherichia coli, and their endotoxins [18] and also other microbes [19].…”
Section: Discussionmentioning
confidence: 99%